BODY CLASSIC BODY MASSAGE FOR SPAZIANO WELFARE (Fiep Bulletin - online, 2019)
Introduction: The history of massage is as old as the art of human healing itself, historical records show the ruins of theimperial baths that presented great benefits to its guests from these ancient SPAs with massages. Objective of this research wasto verify the main benefits cited by authors on the classic body massage for the well-being of Spaziano. Method of research wasthrough a bibliographic review between the year 2001 and the year 2017, with a search of the benefits presented from classicmassage to the Spazian. The databases used were SciELO, PubMed and academic papers, in Portuguese and English. Results,of the 58 surveyed, were used 30, which cited the main benefits: overall satisfaction; increased confidence and pleasure; favorssocial inclusion; improves neuropsicoendocrine systems; increases oxytocin and endorphin and thus reduces the level of stress;Relax the mind; relieves muscle aches and aids in recovery after sports activities; improves muscle function; improves the humanrelationship; has rejuvenating action perceived by massaging; improves cardiac responses with decreasing systolic and diastolicpressure; contributes to motor gains in special cases such as Down's Syndrome; contributes to all phases of life, increasessafety, tranquility and comfort; improves physical disposition, improves relaxation in cancer patients; decreases tension incollege students; decreases edema and decreases body measurements; stimulates circulatory systems; increases metabolicand neuromuscular responses; decreases anxiety and depression; improves self-esteem; contributes to quality of life;considered as excellent complementary therapy; favors greater integration between body and mind; the frequency makes valuethe quality of life. Final considerations: The beneficial results promoted by classical massage are factors to increase thefrequency in the SPA environment by the Spazians to promote well-being and quality of life.
Keywords: MASSAGE; WELL-BEING; RELAXATION.